Prediction of tannin content and quality parameters in astringent persimmons from visible and near-infrared spectroscopy - Baek, Min Woo; Choi, Han Ryul; Hwang, In Geun; Tilahun, Shimeles; Jeong, Cheon Soon (Frontiers in Plant Science, 2023)
Tannin content and postharvest quality characteristics of persimmon fruit are often determined by the destructive analysis that consumes time, does not allow the acquisition of data from the same fruit continuously, and requires expensive high-performance equipment. This research was done to investigate the potential for non-destructive estimation of astringency and quality parameters in persimmon fruit based on visible/near-infrared (VNIR) spectra. VNIR spectra readings, the reference tannin content, and quality parameters were measured from fruits of "Cheongdo-Bansi" and "Daebong" persimmon cultivars at harvest and throughout the ripening/deastringency period. The spectra readings from half of the total fruit were utilized for the calibration set, while the other half readings were used for the prediction set. To develop models correlating the spectra data to the measured reference parameters data, the partial least square regression (PLSR) method was utilized. In the case of 'Daebong', the coefficients of determination (R 2 ) between VNIR spectra and the actual measured values of TSS, firmness, simple sugars, and tannin content were (0.95, 0.94, 0.96, and 0.96) and (0.95, 0.89, 0.96, and 0.93), for the calibration and prediction sets, respectively. Similarly, the R 2 -values of (0.86, 0.93, 0.79, and 0.81) and (0.83, 0.91, 0.75, and 0.75) were recorded in 'Cheongdo-Bansi' for the calibration and prediction sets, respectively. Additionally, the acquired data were divided into two sets in a 3:1 ratio to develop predictive models and to validate the models in multiple regressions. PLSR models were developed in multiple regression to estimate the tannin content of both cultivars from firmness and simple sugars with R 2 -values of 0.83 and 0.79 in 'Cheongdo-Bansi' for the calibration and prediction sets, respectively, whereas, R 2 -values of 0.80 and 0.84 were recorded in 'Daebong' for the calibration and prediction sets, respectively. The overall findings of this study showed the possibility of using VNIR spectra for the prediction of postharvest quality and tannin contents from intact persimmon fruit with quick, chemical-free, and low-cost assessment methods. Also, the multiple regression using physicochemical parameters could fairly predict the tannin content in persimmon fruit though destructively but save time and low-cost.